Broadband time domain diffuse optical characterization of human cadaver bone from 500 to 1100 nm - Suraj Kumar Kothuri; Danielle MacMahon; Pranav Lanka; Carrie O’Flynn; Patrick Henn; Stefan Andersson-Engels; Rekha Gautam; Sanathana Konugolu Venkata Sekar (Scientific Reports)
Abstract Bone is an integral component of the skeletal system, providing structural support and playing a crucial role in metabolic and pathological processes. Understanding its optical properties is essential for uncovering its structural heterogeneity and biochemical composition. However, the optical properties evaluation and biomarker decomposition is challenging due to its highly scattering nature. In this study, we present the optical characterization of fresh cadaveric human tibia bone from an 89-year-old female donor using Time-Domain Diffuse Optical Spectroscopy (TDDOS) technique. Absorption and reduced scattering spectra were obtained at three distinct locations of the tibia, revealing characteristic absorption peaks corresponding to key biomarkers such as oxy-haemoglobin (HbO2), met-haemoglobin (Met-Hb), lipids, collagen. By analysing the optical properties of individual bone constituents, we identified that the 930 nm lipid peak primarily originates from trabecular bone and bone marrow, with minimal contribution from cortical bone. Cortical bone flakes exhibited high reduced scattering coefficients while trabecular bone demonstrated lower scattering values consistent with its porous nature. These findings provide new insights into the heterogeneity of bone tissue and the biomarker distribution within its distinct constituents. This work lays the groundwork for advancing in vivo, non-invasive spectroscopic techniques for deep tissue investigation and improved diagnosis of bone pathologies.